AN ANALYSIS OF THE “RIGHT OF TERMINATION”, “RIGHT OF CANCELLATION” AND “RIGHT OF WITHDRAWAL” IN OFF-PREMISES AND DISTANCE CONTRACTS ACCORDING TO EU DIRECTIVES - GIAMPIERI, Patrizia (Comparative Legilinguistics, 2021)
Several are the European Directives dedicated to e-commerce, focussing on consumer rights, the distance marketing of consumer financial services and the protection of consumers in distance contracts. In contract law, the terms “termination”, “withdrawal” and “cancellation” have peculiar and distinct meaning. Nonetheless, they tend to be misused and applied interchangeably. This article will shed light on these relevant terms in the light of EU Directives on the protection of consumer rights in off-premises and distance contracts. To do so, it will first present instances in which the meaning and use of these terms is either clear-cut or somehow blurred. By analysing word usage and meaning in context, it will explore how EU Directives, and EU drafters in general, made (un)ambiguous distinctions. Then, it will investigate whether English-speaking drafters (such as those of the pre-Brexit UK, Ireland and Malta) made a consistent use of such terms. Finally, this paper will explore whether online conditions of sale written in English by non-English speaking sellers or traders (such as Italian and Polish) also make a consistent use of the terms. The paper findings highlight that the use and legal purpose of these terms in European Directives have not been particularly consistent over the years. Furthermore, Member States’ system-specificity has weighed on the meaning, application and scope of the terms. On the other hand, at EU level the absence of a unique legal system of reference and the challenges of harmonization may have created false equivalences.